Documentary Poetry. A Tendency in Contemporary Norwegian Literature - Wærp, Henning Howlid (Nordlit, 2023)
It is common knowledge that novels and plays can have documentary tendencies, but what about the poem? Many associate poetry with sensation or feeling rather than analysis, thinking or matter. Based on collections of poems by Rune Tuverud, Markus Midré, Freddy Fjellheim, Espen Stueland and others, the genre "sakpoesi" is discussed, as it has emerged in Norwegian literature from the 1990s onwards.